PRONOMINA PERSONA DALAM NOVEL NAIFU DAN TERJEMAHANNYA DALAM BAHASA INDONESIA - Hermawan, Nunung (Japanese Literature, 2013)
Pronouns are a type of word that replaces the noun or noun phrase. One of the personal pronouns to be discussed in this writing is personal pronouns. Demonstrative persona used to call or call someone who is known and not known while communicating at home, school, the office, and a public place in daily life. In addition, demonstrative can also serves as the identity speakers of if observed from talks spoken by speakers of it self. The Japan language prepositional pronouns have clear rules, in determining who is customarily wears the persona pronouns. The use of a personal pronoun based on social condition can be observed from the speakers ' speech is used when someone is communicating. The use of pronouns personal that is uttered by the Japan society, especially young people in conversation each day on a situation that is not official, such as at home, in the streets, in the parks and so forth when a familiar friend, boyfriend, friend, sibling. The use of pronouns persona is also often used in movies, anime, comics, plays, and so on. In Japanese language, demonstrative called by daimeishi, later the personal pronouns persona called ninshou daimeishi. Ninshou daimeishi grouped into three parts those are jishou or pronouns persona first, taishou or pronouns persona second, tashou or pronouns persona third Keywords : daimeishi, ninshou daimeishi, personal pronoun